Gastric outlet obstruction with ascites: EUS-guided gastro-enterostomy is feasible - Basha, Jahangeer; Lakhtakia, Sundeep; Yarlagadda, Raghavendra; Nabi, Zaheer; Gupta, Rajesh; Ramchandani, Mohan; Chavan, Radhika; Jagtap, Nitin; Asif, Shujaath; Rao, Guduru Venkat; Reddy, Nageshwar (Endoscopy International Open, 2021)
Background and study aims Endoscopic ultrasound-guided gastro-enterostomy(EUS-GE) is a recently described novel minimally invasive endoscopic procedure for patients having malignant gastric outlet obstruction (GOO). The safety of EUS-GE in the presence of ascites with GOO is not known. The objective of the study was to evaluate the feasibility and safety of EUS-GE in patients with GOO and ascites.Patients and methods Consecutive patients with GOO who underwent EUS-GE between January 2019 and March 2021 constituted the study population. EUS-GE was performed using either EPASS or free-hand technique. The technical success, clinical success, adverse events, and survival times were evaluated. The outcomes were compared between patients with and without ascites.Results A total of 31 patients with GOO underwent EUS-GE of whom 29 (93.5 %) had malignant and two (6.4 %) had benign etiologies. Ascites was observed in 12 out of 31 (38.7%) patients and all had underlying malignancy. Majority (27, 87 %) of the EUS-GE procedures were performed using EPASS technique, and 4 (13 %) underwent free-hand technique. Eleven of 12 patients with ascites and GOO underwent EUS GE using EPASS technique. The technical success (91.6 % vs. 89.4 %; P = 0.841), clinical success (83.3 % vs. 89.4 %; P = 0.619), mean procedure time (32 vs. 31.6 min; P = 0.968) and adverse events (0 % vs. 10.5 %; P = 0.245) were not significantly different between patients with or without ascites. However, the median survival time was significantly low in patients with ascites when compared to without ascites (36 vs. 290 days; P < 001).Conclusions Ascites is a common occurrence in patients with malignant GOO. EUS GE is feasible in presence of ascites with EPASS technique.